PENGARUH KUALITAS PRODUK, HARGA, PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN TEH CELUP SARIWANGI DI KOTA BOGOR - Wahyu Widayat, Eko; Rahmawati, Nurhasna (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
Tea is one of the refreshing drinks that is very popular among the people of Indonesia and even the world. The purpose of this study was to determine and analyze the effect of product quality, price, promotion and brand image on purchasing decisions for SariWangi brand products in Bogor City. The results of the regression test showed that 62,10% of the purchasing decision factors could be explained by product quality, price, promotion and brand image while the remaining 37,90% were explained by other factors not examined in this study. While the results of the F test show that simultaneously the variables of product quality, price, promotion and brand image simultaneously have a positive and significant effect on purchasing decisions. The results of the t test show that the product quality, promotion, brand image variable so partially these three variables have a positive effect and significantly to the decision to purchase Teh Celup Sariwangi products in Bogor City. The price variable has no positive and significant effect on the decision to purchase Teh Celup Sariwangi products in Bogor City. The dominant variable influencing the purchasing decision of The Celup Sariwangi products in Bogor City is product quality.